2018
DOI: 10.1515/cclm-2017-1099
|View full text |Cite
|
Sign up to set email alerts
|

Sialylated isoforms of apolipoprotein C-III and plasma lipids in subjects with coronary artery disease

Abstract: Specific patterns of ApoC-III glycoforms are present across different total ApoC-III concentrations in CAD patients. The inhibitory effect of ApoC-III on LPL appears related to total ApoC-III concentration, but not to the relative proportion of ApoC-III glycoforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…However, no other significant correlations were found among the analyzed proteoforms. Our results are consistent with those reported by Olivieri et al in a cohort of CAD patients where a negative tendency was reported between Apo CIII0 proteoforms and TG (34).…”
Section: Discussionsupporting
confidence: 94%
“…However, no other significant correlations were found among the analyzed proteoforms. Our results are consistent with those reported by Olivieri et al in a cohort of CAD patients where a negative tendency was reported between Apo CIII0 proteoforms and TG (34).…”
Section: Discussionsupporting
confidence: 94%
“…The physiological relevance of these glycoforms is still unclear, but the degree of sialylation of apoC-III has been proposed to influence lipoprotein lipase (LPL)-mediated hydrolysis of TRLs in the circulation. Recent investigations reveal that the different apoC-III glycoforms show specific patterns over the range of total apoC-III concentration, but the impact of this variation on the atherogenic potential of the apoprotein is unclear [ 7 •].…”
Section: Introductionmentioning
confidence: 99%
“…The application of more specific enrichment methods, such as immunocapture, may help to reduce signals interfering with the various apo-CIII oxidoforms, but was not implemented in the present study for simplicity reasons. Of note, apo-CIII proteoforms have been analyzed by methods employing LC systems (Kailemia et al, 2018;Olivieri et al, 2018). Despite certain advantages over MALDI-TOF MS, such as absolute quantification and enhanced resolution, the throughput of this approach remains relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…Expression levels of apo-CIII were not investigated in this study. The differences in apo-CIII glycosylation profiles observed between individuals may be caused by varying expression levels of apo-CIII (Olivieri et al, 2018) or apo-CIII glycoforms (Holleboom et al, 2011), or the accumulation of certain glycoforms due to dysfunctional clearance pathways, based on recent findings by Kegulian et al (Kegulian et al, 2019). It may also be a combination of the listed factors, which should be explored in further research.…”
Section: Associations Between Apo-ciii Sialylation and Lipid Markersmentioning
confidence: 98%
See 1 more Smart Citation